2014
DOI: 10.1108/ecam-06-2013-0058
|View full text |Cite
|
Sign up to set email alerts
|

Addressing effective construction logistics through the lens of vehicle movements

Abstract: Construction logistics is an essential part of Construction Supply Chain Management (CSCM).However, limited attention has been paid to this issue in the New Zealand construction industry.The purpose of this paper is to contribute to the knowledge about what hampers efficiency in transporting construction materials and plants to a construction site. The intention is to gain detailed understanding of the practice and obstacles in efficient construction logistics and thus identify interventions to improve logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
(13 reference statements)
1
20
0
Order By: Relevance
“…Fei Ying, John Tookey, Johannes Roberti (2014) believe that the intention is to gain detailed understanding of the practice and obstacles in efficient construction logistics and thus identify interventions to improve logistics efficiency, especially using the numbers of vehicle movements to the construction site as an indicator [1]. Viktoria Sundquist (2018) in this research reflected logistics reorganizing can contribute to improved performance in the construction industry.…”
Section: Main Bodymentioning
confidence: 96%
“…Fei Ying, John Tookey, Johannes Roberti (2014) believe that the intention is to gain detailed understanding of the practice and obstacles in efficient construction logistics and thus identify interventions to improve logistics efficiency, especially using the numbers of vehicle movements to the construction site as an indicator [1]. Viktoria Sundquist (2018) in this research reflected logistics reorganizing can contribute to improved performance in the construction industry.…”
Section: Main Bodymentioning
confidence: 96%
“…Materials could be purchased too late causing delays or too early and getting damaged in poor storage conditions on-site [4]. Delivering materials to the site without a timely notice causes extra material handling and labour cost [14]. Proper logistics management requires complete and accurate information regarding the materials and delivery that is communicated between the project parties.…”
Section: Materials Logistics In Constructionmentioning
confidence: 99%
“…Zeng and Rossetti, 2003;Shakantu, et al, 2003;Engblom, et al, 2012;Stock and Lambert, 2001). However, there were indications that the cost for transports could actually be lowered as instead of multiple vehicles arriving to site, one consolidated delivery could take care of the last leg of the journey (see Table 4) (Ying, et al, 2014;Vidalakis, et al, 2011;Vidalakis, et al, 2013). On site, this can reduce the cost of non-productive time as deliveries are coordinated and consolidated, meaning that the craftsmen will not be interrupted as often to receive materials as in the traditional setup (cf.…”
Section: How Will the Use Of Construction Logistics Solutions Affect mentioning
confidence: 99%
“…Ekeskär and Rudberg, 2016;Lindén and Josephson, 2013). However, the costs of implementing and utilizing CLS's are still a source of worry for many construction companies as the logistics costs are to a large extent intangible (Ying, et al, 2014;Fang and Ng, 2011). Paper 4 provides an initial cost modelling effort through activity-based costing (see Table 5, Figure 18), and from this it was shown that there is a way to take control of the costs of CLS's.…”
Section: How Will the Use Of Construction Logistics Solutions Affect mentioning
confidence: 99%